Analisis Perbandingan Kinerja Keuangan Sebelum dan Setelah Penerapan Program Branchless Banking - Ulfi Hidayanti; Leni Nur Pratiwi; Destian Arshad Darulmalshah Tamara (Journal of Applied Islamic Economics and Finance, 2021)
Laku Pandai is a program without financial office services (Branchless Bangking) formed by Otoritas Jasa Keuangan in the context of financial inclusion, can be done in collaboration with other parties (bank agents), supported by the use of information technology facilities. This study aims to describe whether there are significant differences in banking financial performance between before and after the implementation of the Laku Pandai’s program, measured by solvency ratio (CAR), profitability ratios (ROA, BO/PO,GPM and NPM), and liquidity ratios (LDR/FDR). The population used are banks that implement the Laku Pandai’s program. BRI Bank and BRI Syariah Bank are the samples chosen using purposive sampling. The method of data collection in this study is the documentation method. Testing the hypothesis that is by non parametric statistical analysis using Wilcoxon Signed Rank Test (and Mann Whitney test. The results of this study indicate that there are significant differences in CAR, LDR, ROA, BO / PO, GPM and NPM at BRI Bank before and after the implementation of Laku Pandai’s program. At BRI Syariah Bank there are significant differences in CAR, FDR and GPM but in ROA, BO/PO and NPM there is no significant difference between before and after the implementation of Laku Pandai’s program. In addition, between BRI Bank and BRI Syariah Bank after the implementation of the Laku Pandai’s program there were significant differences in LDR/FDR, ROA, BO/PO, and NPM, but there were no significant differences in CAR and GPM.